2021
DOI: 10.1186/s12872-021-02102-6
|View full text |Cite
|
Sign up to set email alerts
|

SLE strikes the heart! A rare presentation of SLE myocarditis presenting as cardiogenic shock

Abstract: Background Although systemic lupus erythematosus (SLE) can affect the cardiovascular system in many ways with diverse presentations, a severe cardiogenic shock secondary to SLE myocarditis is infrequently described in the medical literature. Variable presenting features of SLE myocarditis can also make the diagnosis challenging. This case report will allow learners to consider SLE myocarditis in the differential and appreciate the diagnostic uncertainty. Case pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Current treatment of acute lupus myocarditis is largely empirical, and corticosteroids serve as an important option. [7] In this patient, the signifi cant improvement after large doses of intravenous immunoglobulin and methylprednisolone reflected the need for early diagnosis of lupus myocarditis. Additionally, supportive therapy to improve cardiac function is also indispensable.…”
Section: Discussionmentioning
confidence: 81%
“…Current treatment of acute lupus myocarditis is largely empirical, and corticosteroids serve as an important option. [7] In this patient, the signifi cant improvement after large doses of intravenous immunoglobulin and methylprednisolone reflected the need for early diagnosis of lupus myocarditis. Additionally, supportive therapy to improve cardiac function is also indispensable.…”
Section: Discussionmentioning
confidence: 81%
“…Las manifestaciones cardiacas, presentes hasta en 50% de los casos, incluyen trastornos de la conducción, isquemia, miocardiopatía, valvulopatías y pericarditis. La progresión rápida de estas entidades hasta el shock es rara y potencialmente mortal, inclusive en estadios iniciales de la enfermedad (1)(2)(3).…”
Section: Discussionunclassified
“…A skin biopsy showed that he has lichenoid dermatitis with a granular pattern. These things showed that the patient has SLE myocarditis, which is a response to aggressive therapy of SLE [3].…”
Section: Pericarditismentioning
confidence: 91%
“…Pericardium, myocardium, coronary arteries, and valves, but acute pericarditis is the most common cardiac problem that can affect SLE patients [2]. Cardiac symptoms are different, which include pain, dyspnea, fatigue, leg swelling, and palpitations [3].…”
Section: Introductionmentioning
confidence: 99%